A brief examination of the sustainability of the Lost PLA method - Maestroeni, Marc (Center for Model-Based Cyber-Physical Product Development, 2021)
This work examines the footprint in term of sustainability of the method of casting using 3d printed PLA. The goal is to prove that the method is available for a mass use in the on-site production to save on the emissions (and cost) of the transport of goods in the mass production.